Defending the faith: John Jewel and the Elizabethan church - Ranson, Angela; Gazal, André A.; Bastow, Sarah L. (Early modern studies, 2018)
"Brings together scholars from several disciplines in Reformation studies to examine the life, work, and enduring significance of John Jewel, bishop of Salisbury from 1560 to 1571"--Provided by publisher